Osseointegration Assessment of Multi‐Material Ti6Al4V‐β TCP Implants: An Experimental Study in Rats. Issue 6 (2nd January 2022) - Costa, Mafalda M.; Miranda, Alice; Bartolomeu, Flávio; Carvalho, Óscar; Matos, Sérgio; Silva, Filipe Samuel; Miranda, Georgina
Abstract: In the present study, mono‐ and multi‐material laser textured Ti6Al4V implants are manufactured and characterized in vivo to explore their applicability in orthopedic implants. Laser surface texturing is used for manufacturing grooved Ti6Al4V implants while a pressure‐assisted sintering technique is employed to impregnate beta‐tricalcium phosphate into grooves for an improved bioactivity. After implantation into Sprague Dawley rat's femur for 4 and 12 weeks, bone‐implant fixation and osseointegration are assessed, by performing push‐out tests and histological characterization. Histological characterization showed bone formation around all implants, characterized by immature bone at 4 weeks of implantation and a more mature bone after 12 weeks. The maximum push‐out forces are higher for the textured and multi‐material solution, when compared to non‐textured implants right after 4 weeks of implantation ( p  < 0.05). After 12 weeks, multi‐material implant displayed higher fracture energy when compared to non‐textured implants ( p  < 0.05). Results revealed that laser surface texturing and bioactive multi‐material solutions are highly effective to promote bone regeneration and enhance bone‐implant fixation for further application in orthopedic implants. Abstract : Aiming to evaluate implant fixation, laser surface modification is employed to manufacture mono‐material Ti6Al4V‐textured implants and multi‐material beta‐tricalcium phosphate‐impregnated Ti6Al4V‐textured implants. Right after 4 weeks of implantation, textured, and multi‐material solutions display higher push‐out force, with the latter having higher fracture energy after 12 weeks, when compared with non‐textured implants. Overall, multi‐material implants demonstrate potential to enhance implant–bone fixation.